2019
DOI: 10.1089/ten.tec.2019.0112
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Printing of Tissue Engineering Scaffolds with Horizontal Pore and Composition Gradients

Abstract: This work investigated a new three-dimensional (3D) printing methodology to prepare porous scaffolds containing horizontal pore and composition gradients. To achieve that, a multimaterial printing technology developed in our laboratory was adapted to incorporate pore gradients. Fibers were printed by welding segments with unique material compositions and fiber diameters. Particularly, we focused on the preparation of model composite poly(e-caprolactone)-based scaffolds with radial gradients of particulate hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 37 publications
(47 reference statements)
0
22
0
Order By: Relevance
“…Specifically, outermost sections of 30 wt% HA/PCL demonstrated increased calcium deposition compared to middle sections of 15 wt% HA/PCL and inner sections of pure PCL. 63 In this study, a dose-dependent effect of b-TCP on mineralization and ALP activity was shown. Furthermore, several studies have observed that b-TCP initiates osteogenic differentiation within 3 days.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Specifically, outermost sections of 30 wt% HA/PCL demonstrated increased calcium deposition compared to middle sections of 15 wt% HA/PCL and inner sections of pure PCL. 63 In this study, a dose-dependent effect of b-TCP on mineralization and ALP activity was shown. Furthermore, several studies have observed that b-TCP initiates osteogenic differentiation within 3 days.…”
Section: Discussionmentioning
confidence: 63%
“…84 A similar ceramic dosedependent phenomenon was observed in the radial gradient study by Diaz-Gomez et al, where regions of higher HA composition led to increased calcium deposition, despite significantly lower porosity in the outer regions containing a high HA composition compared to inner regions with lower or no HA content. 63 We have previously demonstrated how 3D printing can be leveraged to fabricate a wide range of complex multiphasic constructs. [49][50][51] As such, the most notable result from this study is that, by altering the porosity and ceramic composition within a construct, one can direct the osteoblastic phenotype of MSCs within distinct regions of the construct to create cell phenotype gradients.…”
Section: Discussionmentioning
confidence: 99%
“…To generate bone scaffolds harboring these transitions, AM strategies have been previously proposed. Bittner et al and Gomez et al have used tricalcium phosphate- or hydroxyapatite (HA)-loaded poly(ε-caprolactone), and produced AM scaffolds with composition gradients, along the scaffold height or within single layers, by varying the filler concentration using separate printheads for each composition, in a multistep process 13 , 14 . Diverse advantages, such as controlling the mechanical properties, degradation rates, and spatial distribution of regenerated bone, were cited among the potentials of such gradients.…”
Section: Introductionmentioning
confidence: 99%
“…To solve problems mentioned above, as an alternative strategy, artificial bone repairing materials have been developed [ [3] , [4] , [5] , [6] ]. The commonly used bone repairing materials mainly include polymer materials, inorganic materials, metals and their composites [ 7 ].…”
Section: Introductionmentioning
confidence: 99%